OPTIMIZING WRITING SKILLS THROUGH DEDUCTIVE AND INDUCTIVE METHODS: A COMPARATIVE STUDY: OPTIMALISASI KETERAMPILAN MENULIS MELALUI METODE DEDUKTIF DAN INDUKTIF: STUDI PERBANDINGAN - Indriyani, Vivi; Fujita, Titiek; Novelly, Yustitiayu (Jurnal Kata, 2025)
Writing is an essential academic skill that needs to be developed to support success in education and future careers. However, the lack of appropriate teaching methods is often the main cause of students' difficulties in developing writing skills. Therefore, teachers need to select and apply appropriate learning methods so that students can achieve optimal learning outcomes. This study aims to compare the effects of deductive and inductive learning methods on students' writing skills. The study used an experimental approach with a quasi-experimental design of the two-group pretest-posttest type. The research subjects consisted of two classes: two experimental classes that used the deductive method and one other class that used the inductive method. The instrument used was a performance test, and data analysis was carried out statistically using SPSS software. The results of the study showed that both deductive and inductive methods were equally effective in improving students' writing skills. However, based on the analysis results, no significant differences were found between the two methods on student learning outcomes in writing learning.